The decomposition method for solving of a class of singular two-point boundary value problems - İnç, Mustafa; Evans, DJ (Taylor & Francis Ltd, 2003)
In this paper, a class of nonlinear singular two-point boundary value problems are solved by using Adomian's decomposition methods. The approximate solution of this problem is calculated in the form of series with easily computable components. Finally, we give a nonlinear numerical example.
Keywords: Adomian decomposition method; Adomian polynomials; singular two-point boundary value problems; Pade approximation